TWO NEW SPECIES OF PSEUDOCERCOSPORA FROM WEST BENGAL - SARBAJNA, K. K. (Indian Phytopathology, 2002)
Two new species of Pseudocercospora-Pseudocercospora odinae on Odina woodier and Pseudocercospora baruipurensis on Mangijera indica-are described and illustrated here.